PREPARATION OF HYPERIMMUNE SERA FOR SARS-COV-2 VIRUS - Nakhanova, G.D.; Chervyakova, O.V.; Shorayeva , K.A.; Zhakypbek , A.S.; Moldagulova , S.U.; Jekebekov , K.K.; Absatova , Zh.S.; Shayakhmetov , E.A.; Omurtay , A.D.; Baiseit , T.I.; Nakhanov , A.K.; Kerimbayev , A.A. (Eurasian Journal of Applied Biotechnology, 2025)
Hyperimmune sera are a primary component of diagnostic test systems utilising enzyme immunoassay to identify specific antibodies against infectious disease pathogens. During diagnostic assay development, hyperimmune sera function as positive controls and enable the generation of standard curves for quantitative measurement of antibody levels. Furthermore, they can be used to assess the sensitivity and specificity of established test systems and to verify novel diagnostic approaches. The objective of this study was to produce hyperimmune serum against SARS-CoV-2. Purified and concentrated virus, in conjunction with adjuvants such as aluminium hydroxide or AddaS03, was employed to immunise animals. Consequently, specific sera exhibiting activity in ELISA at dilutions of 1:1600- 1:3200 and in the diffusion precipitation reaction (DPR) at 1:8–1:32 were acquired. The research demonstrated that the use of concentrated, pure SARS-CoV-2 for animal immunisation, supplemented with adjuvants, is a viable and efficacious approach for generating highly active antibodies.